Design Research on an RME-Based Mathematics Module for Teaching Data Collection and Handling in Primary Schools - Yuhasriati Yuhasriati; Elizar Elizar; Siti Fatimah; Anwar Anwar (FKIP Universitas Lampung, 2026)
Elementary school mathematics education is critical to fostering students' intellectual skills and problem-solving capacities; however, early learners tend to view mathematics, including early conceptions about statistics, data collection, and analysis, as an abstract subject with negligible practical applications to their real lives. Realistic Mathematics Education (RME) would be one remedy, involving students' immersion in rich real-world contexts; however, empirical support for its application to early statistical learning remains limited. This study developed, implemented, and validated an RME-based instructional module on data collection for third-grade students using a design-research methodology (preliminary research, prototyping, assessment) conducted collaboratively with teachers. The module was trialed in two urban primary schools, with evidence gathered from standardized tests, classroom observations, teacher surveys, and student interviews. Quantitative analysis also demonstrated a substantial increase in data-handling ability with mean scores rising from 58% pre-test to 78% post-test, t(51) = 6.72, p < .001, mean difference = 20.0 percentage points (SE = 2.98; 95% CI [14.02, 25.98]), Cohen's dz = 0.93, an effect size reflecting a large effect. In addition, the McNemar test showed a significant increase in the proportion of students meeting the minimum mastery-learning criteria following the intervention. Qualitative observations indicated increased engagement, more balanced collaborative problem-solving, and improved mathematical exposition. The teacher's response showed relevance and practicality but also raised concerns about time management and a preference for more differentiated tasks for advanced learners. These findings confirm the value of RME in enhancing early pupils' statistical ability, but also reveal a continuing need for iterative design supported by active contributions from teachers. Future work should examine long-term retention and scalability across diverse school contexts. Keywords: RME, mathematics module, data collection, primary students.